The Alliance of Bioversity International and CIAT annual report 2024: Adding up impact: 5 years of food systems transformation - International Center for Tropical Agriculture; Bioversity International (2025)
Discover how the Alliance Bioversity International and CIAT is transforming food systems in its 2024 Annual Report. This collection highlights multiple areas of impact: driving community level change, scaling up innovation to institutions, and shifting policy and practice.